Rebuilding From Conflict: Economic And Social Perspectives In The PDET Municipalities Of Tolima - Luis Fernando Narano Naranjo , Oscar Andrés Benavides Parra , Olga Patricia Pulido Villamil (Migration Letters, 2022)
Widespread violence in territories has negative economic and social intertemporal effects, which increase significantly when in a context of armed conflict, as is the case in Colombia. In this sense, it is inferred that reducing conflict and supporting the recovery of the areas most burdened by conflict should be consistent with improving economic and social behavior. To understand the impact of the armed conflict on the economic behavior of the PDET municipalities located in southern Tolima, a model was proposed that aims to explain the effect of conflict victim cases on the added value gap of the PDET municipalities in Tolima. The cor[1]relation between the original variables is calculated and it is evident that the correlation between the variables suggests a moderately strong inverse relationship; which could be interpreted as an indication that an increase in local economic activity may be associated with greater social stability and possibly lower levels of violence.